Réponses

2014-06-15T15:58:53+02:00
S = b-(a+d)-c

a) 
S = 4-(10-8)-6
S = 4-2-6
S = 4-8
S = -4

b)
S = 3-(-7+2)-(-1)
S = 3+5+1
S = 9


c
S = 7-(-6-10)-(-3)
S = 7-(-16)+3
S = 7+16+3
S = 26
2014-06-15T16:03:19+02:00
S = b - (a + d) - c

a)  S = 4 - (10 - 8) - 6
S = 4 - 2 - 6
S = -4

b) S = 3 - (-7 + 2) + 1
=3 +5 + 1
= 9

c) S = 7 - (-6 - 10) + 3
= 7 +16 + 3
= 26


- et - donne +
merci davoir pris le temps de m'expliquer
avec plaisir ;-)
l'essentiel c'est que tu comprenne bien ;-)
si tu as d'autre question n'hesite pas